Propriedades físicas e mecânicas de um cimento de ionômero de vidro após a incorporação de nanopartículas de dióxido de titânio - Cunha, Juliana Maria Albano [UNESP] (2014)
The addition of nanoparticles to dental materials mainly searches to improve the antibacterial properties without changing their mechanical and physical properties. The aim of this study was to evaluate the influence of the incorporation of titanium dioxide (TiO2) nanoparticles to conventional glass ionomer cement (GIC) (Ketac Molar EasyMix) on mechanical (Vickers hardness and compressive strength) and physical (roughness and porosity) properties. For all experiments four groups (n=10) were used: control (without addition of nanoparticles), 1%, 2%, 5% (w/w) of TiO2. The Vickers hardness was measured using a digital hardness (Micromet 2100), compressive strength using a universal testing machine (EMIC-DL 2000), the roughness using a profilometer (Mitutoyo SJ-400) and for porosity, images were made using scanning electron microscopy (SM-300) and analyzed by Image J-software. The data were analyzed by one-way ANOVA and Tukey's post hoc test, with the level of significance set at 5%. There were statistically significant differences for the experiments of Vickers hardness (p ≤ 0.001) and roughness (p = 0.010). We observed that the GIC containing 1% or 2% of nanoparticles had lower values for hardness and the surface roughness was lower by adding 2% and 5% of nanoparticles. SEM images showed no significant changes in surface morphology of the GIC. The addition of 5% (w/w) TiO2 nanoparticles to conventional GIC provides promising results, since it does not compromise the physical and mechanical properties and improves surface roughness. The addition of TiO2 nanoparticle to Ketac Molar EasyMix suggests clinical indication.